1947
DOI: 10.1152/ajplegacy.1947.148.1.152
|View full text |Cite
|
Sign up to set email alerts
|

The Increase in Hypoxia Tolerance of Normal Men Accompanying the Polycythemia Induced by Transfusion of Erythrocytes

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

1947
1947
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…Unfortunately, the animals were made anemic, thus adding to the objections above those of iatrogenic alterations of oxygen delivery such as decreased end-capillary Po2 (18), altered cardiac output, and a possible shift towards anaerobic metabolism in low-P50 animals (19). Not surprisingly, conflicting results have also come from models employing polycythemia (20)(21)(22)(23), which has complex effects on oxygen delivery (24).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the animals were made anemic, thus adding to the objections above those of iatrogenic alterations of oxygen delivery such as decreased end-capillary Po2 (18), altered cardiac output, and a possible shift towards anaerobic metabolism in low-P50 animals (19). Not surprisingly, conflicting results have also come from models employing polycythemia (20)(21)(22)(23), which has complex effects on oxygen delivery (24).…”
Section: Resultsmentioning
confidence: 99%
“…Autologous erythrocyte infusion has been shown to increase Hct, Hb concentration and c a O 2 (Pace et al 1947;Buick et al 1980;Robertson et al 1982Robertson et al , 1988. In the present study, infusion of 700 ml of saline with autologous erythrocytes (42% Hct) resulted in higher (P < 0.05) arterial Hct (+9%), arterial Hb concentration (+10%), and a smaller decrease (P < 0.05) in c a O 2 for the ER compared to the CON group during acute exposure (1st day) at high altitude Young et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Pace et al (1947) showed that young men infused with 1000 ml of erythrocytes (Hct + 20%) displayed lower HR while treadmill walking in hypoxic (hypobaric chamber) conditions simulating exposure to an elevation of 4712 m when compared to non-infused controls walking under the same conditions. They concluded that blood doping lowered one's``physiological'' altitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ergogenic effect of blood transfusions has been clearly proven for almost 60 years, and although the detection of homologous transfusions has recently been confirmed, the detection of autologous transfusions has not yet been resolved [1,2]. The direct detection method used for homologous transfusions, which is based on testing for differences between antigens, cannot be logically used in the case of autologous transfusions.…”
Section: Introductionmentioning
confidence: 99%